Why Is Math Cheaper than English? Understanding Cost Differences in Higher Education - Hemelt, Steven W.; Stange, Kevin M.; Furquim, Fernando; Simon, Andrew; Sawyer, John E. (Journal of Labor Economics, 2021)
This paper establishes five new facts about instructional costs in higher education using department-level data from a broad range of institutions. Costs vary widely across fields, ranging from electrical engineering (90% higher than English) to math (25% lower). This pattern is largely explained by differences in class size and faculty pay. Some STEM fields experienced steep declines in expenditures over the past 17 years, while others saw increases. Changes in class size and teaching loads alongside a shift toward contingent faculty explain these trends. Finally, the association between online instruction and instructional costs is statistically indistinguishable from zero.